A synthesis of the prevalence and drivers of non-compliance in marine protected areas. (March 2021) - Iacarella, Josephine C.; Clyde, Georgia; Bergseth, Brock J.; Ban, Natalie C.
Abstract: Non-compliance regularly negates the effectiveness of marine protected areas (MPAs) worldwide. Understanding and addressing non-compliance is critical given continued efforts to establish MPAs to meet international milestones (e.g., Aichi targets). We conducted a literature review and meta-analysis to address five key questions and research gaps for MPAs: 1) how is non-compliance best measured? 2) what are common drivers of non-compliance? 3) what is the overall prevalence of non-compliance? 4) how frequently is ecological failure of MPAs attributed to non-compliance? and 5) are there measurable management impacts on regulated fishing in MPAs (i.e., effective reduction of fishing)? We found 151 papers that had some focus on non-compliant resource extraction in MPAs and 96 that quantified it. Insufficient enforcement was the most cited driver of non-compliance, followed by several socio-economic drivers including lack of awareness, livelihood/economic gain, social norms, and ineffective governance. Prohibited fishing in MPAs was often reduced compared to outside areas, as shown by our meta-analysis. However, we found frequent reports and measures of non-compliance globally, and many cases of failed ecological performance attributed primarily to non-compliance (57% of 67 relevant studies). Overall, our synthesis demonstrates that non-compliance continues to be a prevalent issue for MPAs. Reducing non-compliance and ensuring effective MPAs will rely on continuous evaluation of non-compliance to inform adaptive management, as well as addressing the complex, interrelated drivers that arise throughout MPA planning, establishment, and management. Highlights: Non-compliant fishing impedes the effectiveness of marine protected areas (MPAs). Quantitative methods to measure non-compliance are increasing and improving. Insufficient enforcement and socio-economic factors are common drivers of poaching. Poaching is prevalent globally and is a major reason for failed MPA performance. Monitoring non-compliance is imperative for ensuring effective MPAs.